Nilai Ekonomi Islam: Dinamika Biaya Transaksi Petani Tambak Ikan Simba dalam Memenuhi Kesejahteraan Rumah Tangga: Studi Kecamatan Padang Cermin Kabupaten Pesawaran - Rintan Ade Puspita; Ghina Ulfah Saerrohman; Alief Rakhman Setyanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The dynamics of transaction costs faced by Simba fish farmers in their efforts to improve household welfare are examined from an Islamic economic perspective. Transaction costs arising in production and distribution activities, such as information search costs, negotiation costs, implementation costs, licensing costs, transportation costs, and maintenance costs, often hinder farmers from obtaining optimal income.  This condition has implications for the welfare of fish pond farming households, particularly in Padang Cermin Subdistrict, Pesawaran Regency, where most of the community depends on the fish pond farming sector for their livelihood. This study aims to analyse the forms and dynamics of transaction costs faced by simba fish pond farmers, assess their impact on household welfare, and review these practices based on Islamic economic principles. The research method used is a qualitative approach with field research.  In this study, the primary data in Padang Cermin Subdistrict, Pesawaran Regency, consisted of 10 fish farmers. Data collection techniques were carried out through in-depth interviews, observations, and documentation of simba fish farmers, collectors, and related parties. Data analysis was carried out descriptively and qualitatively using an Islamic economic approach. The research method used was a qualitative approach with field research. In this study, the primary data was collected from 10 fish farmers in Padang Cermin Subdistrict, Pesawaran Regency. Data collection techniques were conducted through in-depth interviews, observations, and documentation of Simba fish farmers, collectors, and related parties. Data analysis was conducted using descriptive qualitative analysis with an Islamic economic approach. The results showed that high transaction costs, mainly due to dependence on middlemen, price information asymmetry, and the weak bargaining position of farmers, had a negative impact on the welfare of fish farmers' households. From an Islamic economic perspective, unfair transaction costs that tend to harm farmers are contrary to the principles of justice (al-‘adl), benefit (maslahah), and prohibition of exploitation (zulm). Therefore, it is necessary to strengthen farmer institutions, market transparency, and the application of Islamic economic values.